2018
DOI: 10.1016/j.amsu.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Violence against doctors, a serious concern for healthcare organizations to ponder about

Abstract: BackgroundAggression and Violence against primary care physicians is reportedly common in Pakistan but there is no any documented study to-date on this burning issue.MethodsA formed written questionnaire was distributed among 769 primary care physicians aged 31 ± 7.68 years. Apart from the demographic data, the questionnaire included questions regarding the level of safety that primary care physicians felt during their work setups and on-call duties, along with the experience of aggression against them by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 12 publications
(26 reference statements)
6
19
0
3
Order By: Relevance
“…Our study reports different types of violence that healthcare workers experience on a regular basis. In accordance with previous studies, emotional violence is the most prevalent form experienced [5, 11, 43, 63], and patients are the main source of violence against healthcare staff [20, 70, 71].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study reports different types of violence that healthcare workers experience on a regular basis. In accordance with previous studies, emotional violence is the most prevalent form experienced [5, 11, 43, 63], and patients are the main source of violence against healthcare staff [20, 70, 71].…”
Section: Discussionsupporting
confidence: 88%
“…Research in many countries, including Italy [20], indicates that workers in all sectors of healthcare are exposed to workplace violence [25] but that psychiatric [67] and emergency departments are the areas at greatest risk of patient and visitor violence [10], due to several factors that involve both patient pathology and the way services are organised and delivered [20]. Emergency departments are the areas that see the highest rates of patient or visitor violence [43, 54, 68]. The emergency ward is characteristically a high-pressure environment across the 24 hours of the day and experiences a high turnover of patients [37].…”
Section: Introductionmentioning
confidence: 99%
“…4 Investigators have yet to identify experimental approaches that comprise an applicable model to mitigate WPV risk reduction and to identify the underlying mechanisms and antecedent factors. 10 It is also improbable that a basic, “one-size-fits-all” model can be developed as a method for violence prevention. 10,11 Even though violence prevention training is widely available for employees, this has been unsuccessful so far in reducing rates of occurrence for WPV.…”
Section: Introductionmentioning
confidence: 99%
“…These are only a fraction of much more common milder types of HCWPV which comprise of verbal abuse, bullying, intimidation, mental harassment, sexual harassment, and such physical assaults which involve manhandling and beating. [1][2][3][4][5][6] An analysis of data for more than 1,50,000 nurses drawn from 160 global samples has revealed that two third have experienced nonphysical assault while a third were physically assaulted. 2 Physical violence was reported to be more common in the -Anglo‖ and -Anglicized‖ regions i.e.…”
mentioning
confidence: 99%